Development of an analytical model of transient aerodynamic loading for assessing the stability of tower crane metal structures - Gorbatyuk, Ievgenii; Bulavka, Oleg; Terentiev, Oleksandr; Borodynia, Vitalii; Sliusar, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates metal structures of tower cranes that are subjected to intense dynamic impact of the high-speed pressure of extreme wind flow. The task addressed relates to the insufficient adaptability of existing engineering standards (in particular EN 13001-2) to the assessment of crane stability under short-term extreme aerodynamic loads (squall gusts and remote explosion effects). Classical methods use averaged quasi-static coefficients and do not take into account the synergistic effect of the coincidence of the sudden flow vector with the dynamics of pendulum oscillations of the load. The results include the analytical model of velocity head built to describe dynamic loads on the boom, tower, and crane load depending on their position. Aerodynamic coefficients for lattice structures have been determined by taking into account a change in the Reynolds number when the flow front passes. It is shown that the loss of stability is due to the nonlinear interaction of the velocity head with pendulum oscillations of the load and the resistance of the lattice. The maximum overturning moment (up to 451 kNm at a flow velocity of 33 m/s) occurs when the flow velocity vector coincides with the movement of the cargo. Special features of the results involve modification of the classical formula of aerodynamic pressure by integrating the quadratic set of relative velocities. This, in contrast to static approaches, makes it possible to analytically describe the nonlinear amplification of the overturning moment due to the kinetic energy of the swinging cargo under conditions of unsteady flow. The scope of and conditions for practical implementation of the results include engineering and supervisory organizations. The model could be integrated into automated design systems for developing emergency protection algorithms at facilities with an elevated risk of extreme wind loads